Anesthetic Management in Pediatric Patient for Percutaneous Endoscopic Gastrostomy with Mitochondrial Myopathy: Leigh Syndrome - Kiliç, Ebru Tarikçi (Anesth Essays Res, 2018)
Leigh syndrome (LS) is a rare disease mainly affecting the central nervous system due to the abnormalities of mitochondrial energy generation and seen in early childhood with progressive loss of movement, mental abilities, seizures, nystagmus, ophthalmoparesis, optic atrophy, ataxia, dystonia, or respiratory failure. Anesthesia and surgery exacerbate the risks of aspiration, wheezing, and breathing difficulties. Tracheal irritability can be stimulated with the efforts of intubation. We report the anesthetic management of a rare case of an 11-year-old boy with a severe form of LS for percutaneous endoscopic gastrostomy insertion. The patient was closely monitored during the procedure and the postoperative period. Carefully chosen anesthetic agents, good pain control, and close monitoring are essential.